The value of powdery mildew resistance in grapes: Evidence from California - Kate B. Fuller; Julian Mark Alston; Olena S. Sambucci (Wine Economics and Policy, 2014)
Powdery mildew (PM) is a fungal disease that damages many crops, including grapes. In California, wine, raisin, and table grapes contributed over 3.9 billion to the value of farm production in 2011. Grape varieties with resistance to powdery mildew are currently being developed, using either conventional or transgenic approaches, each of which has associated advantages and disadvantages. PM-resistant varieties of grapes could yield large economic benefits to California grape growers-potentially allowing cost savings as high as 48 million per year in the subset of the industry covered by our analysis (Crimson Seedless table grapes, all raisin grapes, and Central Coast Chardonnay wine grapes), but benefits range widely across the different grape production systems.
Keywords: 330; California grapes; Powdery mildew; Research benefits; Resistant varieties